Rapid-onset neovascular glaucoma following cataract surgery in diabetes: outcomes of pars plana vitrectomy combined with Ahmed glaucoma valve implantation - Hui-Ping Yao; Ya-Nuo Wang; Yan-Wei Chen; Sha Gao; Yi-Sheng Zhong; Xi Shen (International Journal of Ophthalmology)
AIM: To present a case series of rapid-onset neovascular glaucoma (NVG) accompanied by vitreous haemorrhage (VH) following cataract surgery in diabetic patients, and to evaluate the efficacy of pars plana vitrectomy (PPV) combined with Ahmed glaucoma valve (AGV) implantation. METHODS: This is a retrospective, single-center, consecutive case series. All patients underwent 23-gauge PPV with AGV implantation 2–3d after intravitreal ranibizumab injection (IVR). The minimum postoperative follow-up period lasted 12mo. The primary outcome measures included best-corrected visual acuity (BCVA), intraocular pressure (IOP), and topical hypotensive medications. RESULTS: Fifteen diabetic patients (age, 46–81y) with rapid-onset NVG and VH following uncomplicated phacoemulsification were included. The median time to the initial NVG diagnosis following cataract surgery was within 4wk. After PPV combined with AGV implantation, the mean BCVA (logMAR) improved from 1.9 (range: 1.0 to 2.6) preoperatively to 1.2 (range: 0.2 to 2.6) at the final follow-up. Baseline BCVA and the presence of diabetic nephropathy (DN) were significantly associated with the final BCVA in the multiple regression model. The mean postoperative IOP at all follow-up visits was significantly reduced compared to baseline. At the final follow-up, 9 patients required one or two topical ocular hypotensive medications, while the other 6 needed not. Success was achieved in 87%, and the reoperation rate was 20%. The majority of NVG cases (9/15) were primarily attributed to the rapid progression of proliferative diabetic retinopathy. However, a notable subset (6 eyes) was complicated retinal vein occlusion or carotid artery occlusion. CONCLUSION: PPV combined with AGV implantation after adjuvant IVR for rapid-onset NVG with VH following diabetic cataract surgery is one of the safe and effective treatments. Baseline BCVA and preexisting DN may be potential indicators for visual outcomes.